Do fair adjustments influence dividend policy for South African firms? - Grimmer, Brian (Department of Finance and Tax, 2017)
This paper investigates the potential procyclical effects of fair value accounting (FVA). If FVA adjustments result in increased accounting profits with the recognition of transitory gains through a firm's profit and loss (P&L), and if management incorrectly assesses the persistence of the unrealised gains, these increased profits may be paid out as dividends. This has the potential to increase leverage and risk for these firms, thereby also possibly amplifying economic cycles. A study by Goncharov and Van Triest (2011:59) on Russian firms found that FVA adjustments are persistent in future earnings; however, no empirical evidence was found to support an increase in dividends in response to unrealised FVA gains. By contrast, when the setting is limited to South African banks only, De Jager (2015:157) found that South African banks have paid the full amount of any unrealised transitory gains as dividends. This study focuses on the effects of FVA adjustments on dividend policy for South African firms, as represented by the firms included in the FTSE/JSE Top 40 Index. This furthers De Jager's (2015) study by extending the investigation of the dividend relevance of FVA adjustments from the major South African banks, to South African large firms in general. The results of a panel regression of the net profit of these firms reveal that unrealised FVA adjustments do have a persistent influence on future earnings, indicating that these adjustments contain both transitory and persistent elements. A further panel regression of the annual dividends declared by these firms indicates that dividend payments do include a portion of unrealised FVA gains, as expected by the persistent nature of a portion of these unrealised FVA gains.